Repensando el poder de las disqueras: el caso de las industrias de la música tropical y la canción romántica en Medellín en los años sesenta - Carolina Santamaría Delgado; Juan Sebastián Ochoa Escobar; Amparo Álvarez García; Federico Ochoa Escobar; Juan Pablo Lopera Londoño (Resonancias, 2020)
The article analyzes how the repertories of música tropical and canción romántica operated within Medellín’s record industry during the 1960s. The study unfolds the idea that each repertoire constitutes by itself a distinct industry that functions according to its own rationale, and therefore the connections among actors in the local music industry (record companies, radio stations, live music venues, music commentators, record shops) varied in consequence. Taking as reference the vertical integration model developed by authors who have analyzed the production of musical hits in Europe and the US in that period, the study reveals the distinctive features of the Colombian context and questions common-sense interpretations that allocate excessive power to the entertainment industries in the 1960s over the audience’s musical tastes. For this, we conducted a systematic examination of a daily show-business column published in the local newspapers at the time, and combined both qualitative and quantitative research methods.